The Rehnquist Court and the Groundwork for Greater First Amendment Scrutiny of Intellectual Property - Mark P. McKenna (Washington University Journal of Law & Policy, 2006)
In the last few years, many pages have been devoted to retrospectives on Justice Rehnquist and the Rehnquist Court, a fair number of which focused on Justice Rehnquist’s First Amendment jurisprudence. I focus here not on Justice Rehnquist specifically, but on the Supreme Court as a whole during Rehnquist’s tenure. Specifically, I want to address the Court’s view of the role of the First Amendment in intellectual property cases. My thesis is a modest one: while one certainly cannot describe the Rehnquist Court as eager to find a conflict between intellectual property laws and the First Amendment, there is reason to believe that it set the stage for greater First Amendment scrutiny of intellectual property protections. At the very least, the Court left that road open to future courts, which might be inclined to view intellectual property more skeptically.
Keywords: First Amendment protections (United States Constitution); Intellectual property; William H. Rehnquist; 1924-2005; United States. Supreme Court; Commercial speech doctrine; Intellectual property law; United States Constitution; United States